On the Antillean spiders of the genus Scytodes Latreille, 1804 (Araneae, Scytodidae) - Iost, Flora Maria; Alayón, Giraldo; Rheims, Cristina Anne (Zootaxa, 2025)
In this paper, we revise specimens of the genus Scytodes Latreille collected during the Caribbean Biogeography Project (CarBio) on several Antillean islands. Of a total of 480 vials, 199 contained only juveniles that could not be identified to species level. The remaining 281 included specimens of 13 species: the previously known S. blanda Bryant, 1940, S. cubensis Alayón, 1977, S. fusca Walckenaer, 1837, S. longipes Lucas, 1844, and nine species herein described: S. coltrainei sp. nov. (♀) and S. joniae sp. nov. (♂♀) from the Dominican Republic; S. harissoni sp. nov. (♀) from Saint Martin; S. jimmorrisoni sp. nov. (♀), S. mingusi sp. nov. (♂♀), and S. reinhardti sp. nov. (♂♀) from Puerto Rico; S. nicksae sp. nov. (♀) from Jamaica; S. ritae sp. nov. (♀) from Martinique; and S. sabbath sp. nov. (♀) from Cuba. The male originally described as S. cubensis is regarded as a misidentification, and a new male is described based on our material. The species is newly recorded from Puerto Rico, Jamaica, and the Dominican Republic. Scytodes blanda is newly recorded from Grenada and Saint Vincent and the Grenadines, and both S. blanda and S. cubensis are redescribed. Scytodes fusca is recorded from Cuba, the Dominican Republic, Puerto Rico, Saint Martin, Bonaire, St. Eustatius and Saba, Dominica, Martinique, Saint Lucia, Barbados, and Saint Vincent and the Grenadines. Scytodes longipes is recorded from Cuba, Puerto Rico, the Dominican Republic, Jamaica, Saint Martin, Saint Kitts and Nevis, Dominica, Martinique, Saint Lucia, and Saint Vincent and the Grenadines. Scytodes darlingtoni Alayón, 1977 is redescribed from the holotype. Updated distribution maps are provided for all species, and additionally, we describe a new type of female genitalia observed only in island-inhabiting species.